Assessment of Heavy Metals in Seawater and Sediment, and Their Implications for Sea Salt Farming in La Union, Philippines - Tabafunda, Junifer Rey (International Journal of Environmental, Sustainability, and Social Science, 2026)
When heavy metals contaminate coastal resources and threaten food safety, marine pollution constitutes a growing challenge to the sustainability of traditional salt farming. Two coastal barangays, Paraoir and Almeida, in Balaoan, La Union, Philippines used in this study to determine the heavy metals in seawater, sediments, and produced salt. Results showed that seawater passed the standards set by the Philippines’s Department of Environment and Natural Resources (DENR) for fishery water for the propagation and growth of fish and other aquatic resources including salt. Higher concentrations of lead (Pb), inorganic arsenic (i-AS), and cadmium (Cd) was found in Paraoir sediments compared with Almeida. Samples of harvested salt proved that mercury (Hg) and Cd were not present, and traces of i-As were recorded within the allowable levels set by the Codex Standards. However, Pb levels in salt samples ranged from 4.03 to 5.45 mg/kg which did not meet the Codex standards for food-grade salt and suggest potential health concerns if consumed frequently. The presence of Pb in sediments in Paraoir could be related with human activities which include processing from cement plant and residues from fishing boats. The study suggests the need for strict implementation of coastal resource management particularly in pollution control and environmental monitoring. The need to improve the post-harvest practices is essential to ensure the health of consumer while sustaining the traditional salt farming as livelihood of the communities in the coastal area.